2013
DOI: 10.1002/ange.201208926
|View full text |Cite
|
Sign up to set email alerts
|

Modular Synthesis, Orthogonal Post‐Functionalization, Absorption, and Chiroptical Properties of Cationic [6]Helicenes

Abstract: Orthogonale elektrophile und nucleophile aromatische Substitutionen ermöglichen die Synthese und selektive Funktionalisierung neuartiger kationischer Diaza‐, Azaoxo‐ und Dioxo[6]helicene (siehe Schema). Reduktionen, Kreuzkupplungen oder Kondensationen erhöhen die Diversität zusätzlich und öffnen einen Zugang zu Spezies mit Absorptionen bis in den Nahinfrarotbereich. Die Diaza‐Salze können als einzelne Enantiomere erhalten werden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Two synthetic pathways to helicenium ions have been reported. A stepwise route, in which a xanthone‐like structure is formed and then treated with a carbon nucleophile to incorporate the third arm into the structure,7e, 10 or a direct route, in which the molecular framework is initially formed and then bridged by either external attack by primary amines or internal attack by hydroxy groups released by ether cleaving reagents 7a. 9a, b, d, 11c, 17 In this work, DMCA + was synthesised by the second route, as presented in Scheme .…”
Section: Resultsmentioning
confidence: 99%
“…Two synthetic pathways to helicenium ions have been reported. A stepwise route, in which a xanthone‐like structure is formed and then treated with a carbon nucleophile to incorporate the third arm into the structure,7e, 10 or a direct route, in which the molecular framework is initially formed and then bridged by either external attack by primary amines or internal attack by hydroxy groups released by ether cleaving reagents 7a. 9a, b, d, 11c, 17 In this work, DMCA + was synthesised by the second route, as presented in Scheme .…”
Section: Resultsmentioning
confidence: 99%
“…[11] Yet, the neutral radical state of the DMQA system has so far not been reported. Structural analogues to these carbenium ions are the neutral, nitrogen-centred [4]heterohelicenes first reported by Hellwinkel et al, [12] and Venkataraman et al later reported and studied the [5]-and [6]heterohelicenes in detail.…”
Section: Introductionmentioning
confidence: 97%
“…The [4]helicenium ion with two oxa bridges (N-alkyl-1,13-dimethoxychromenoxanthenium, DMCX + ) and the asymmetrical derivative with one aza and one oxa bridge (1,13-dimethoxychromenoacridinium, DMCA + ) have since been reported. [3][4][5] Recently, the first synthesis of [6]helicenium ions was achieved, albeit without methoxy groups in the positions equivalent to 1 and 13 in the [4]helicenium structure. [6] DMQA + is a highly configurationally stable, chiral, cationic dye.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Comparatively less studied are cationic helicenoids ( Figure 1). [16][17][18][19][20][21][22][23][24][25][26][27][28] Representative examples are heterohelicenium systems studied by Lacour group 20 or helical dications called helquats developed by our group. 23 These and similar cationic systems promise attractive range of properties and applications [29][30][31][32][33][34][35][36][37][38] that may be complementary to non-ionic helicenes.…”
Section: Introductionmentioning
confidence: 99%